Socio-Pedagogical Analysis Of The Influence Of Axiological Relations On Students On The Basis Of Social Opinions (Eurasian Research Bulletin, 2024)
This paper presents a socio-pedagogical analysis of the influence of axiological relations on students based on social opinions. Axiological relations, encompassing societal values and educational practices, play a significant role in shaping students' identities, attitudes, and behaviors. Through an exploration of societal values, educational practices, and student experiences, this analysis sheds light on the complex interplay between societal influences and individual development within educational contexts. The implications for educational theory, practice, and policy are discussed, emphasizing the importance of promoting critical reflection, dialogue, and ethical reasoning to foster inclusive and equitable learning environments.